Military and Political Integration of Russia and Kazakhstan as a Factor of Strengthening Bilateral Cooperation - Shapkin, M N (Vestnik Rossijskogo universiteta družby narodov. Seriâ Politologiâ (Online), 2016)
The article deals with the modern stage of military and political relations between Russia and Kazakhstan. The role of Organization of the Collective Security Treaty and the Shanghai Cooperation Organization in the fight against international terrorism is emphasized in the article. The article contains a profound analysis of main agreements between the Russian Federation and the Republic of Kazakhstan and therefore defines areas of bilateral cooperation. It is concluded that the main areas of cooperation are the fight against international terrorism, strengthening of military capabilities, and the joint exploration of outer space.